Carbon nanotubes added to Portland cement pastes containing nano-silica - Mendes, Thiago Melanda; Repette, Wellington Longuini (Acta Scientiarum. Technology, 2022)
This study assesses the effect of size, as well as binary and ternary mixtures of three different carbon nanotubes added to Portland cement pastes containing nano-silica. Carbon nanotubes were characterized in terms of size and morphology by transmission electron microscopy, particle size distribution by laser granulometry and electroacoustic attenuation spectroscopy and specific surface area by gas adsorption. The combination of more than one characterization technique helps to identify the finer or coarser carbon nanotube suspensions. The use of low amount of carbon nanotubes and nano-silica does not affect the rheological properties of cementitious matrices. The compressive strength decreases, but flexural strength improves for the finer carbon nanotube. The microstructural analysis showed the adherence of carbon nanotubes on the surface of matrix´s particles, and the nucleation of hydration products on the surface of carbon nanotubes.